Use Your Own Device (UYOD) guidelines as a mechanism to enable sustainable mobile learning in a higher education institution - Igbrude, Claudia (2018)
Despite significant research activity around mobile technologies and growing awareness of the potential of the mobile technologies for education, higher education institutions have not seen mobile learning happen on a large scale and in a sustainable manner. There is no guidance on how to create an environment that enables the use of personally owned devices in learning contexts to enable innovation in teaching practices in higher education institutions. There are many frameworks to guide the implementation of mobile learning initiatives in higher education institutions and evaluate the success of such initiatives. However, none of these frameworks or models provides a roadmap that considers all the processes systems, infrastructure and the people involved to incorporate a Use Your Own Device(UYOD) approach, which then helps to create an ecosystem where the use of mobile technologies to support learning and teaching is enabled. The frameworks also do not take into account the rapidly evolving nature of mobile device capability and the impacts of this on affordances that may be harnessed in learning and teaching contexts.